Single Dose Toxicity of Chukyu (spine-healing) Pharmacopuncture Injection in the Muscle of Rats - Jeong Hohyun; Cho Seung-Hun; Lee Eun-Yong; Lee Seung-Deok; Ahn Seong-Hun; Kim Sungchul (Korean Pharmacopuncture Institute, 2014)
Objectives: This study was performed to analyze the single dose toxicity of Chukyu (spine-healing) pharmacopuncture. Methods: All experiments were conducted at the Biotoxtech, an institution authorized to perform non-clinical studies under the regulations of Good Laboratory Practice (GLP) regulations. Sprague-Dawley rats were chosen for the pilot study. Doses of Chukyu (spine-healing) pharmacopuncture, 0.1, 0.5 and 1.0 mL, were administered to the experimental groups, and a dose of normal saline solution, 1.0 mL, was administered to the control group. This study was conducted under the approval of the Institutional Animal Ethic Committee. Results: No deaths or abnormalities occurred in any of the four groups. No significant changes in weight, hematological parameters or clinical chemistry between the control group and the experimental groups were observed. To check for abnormalities in organs and tissues, we used microscopy to examine representative histological sections of each specified organ; the results showed no significant differences in any of the organs or tissues except in one case, where interstitial infiltrating macrophages were found in one female rat in the 0.5-mL/animal experimental group. Conclusion: The above findings suggest that treatment with Chukyu (spine-healing) pharmacopuncture is relatively safe. Further studies on this subject are needed to yield more concrete evidence.